Handbook of Mobile Teaching and Learning 2018
DOI: 10.1007/978-3-642-41981-2_9-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Devices for Learning and Student Support in the Pacific Region

Abstract: material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Today, education relies heavily on ICT, with new tools in the field of higher education [7][8][9]. For instance, distance learning is not a challenge anymore with off-campus students accessing learning resources using e-learning and m-learning tools [10][11][12][13][14]. In addition to this, AI is gaining interest as it can be used to execute tasks normally associated with human intelligence [15,16], such as social networking applications for learning, speech recognition, learning management systems (LMS), decision-making, cloud learning services, visual perception, mobile learning applications and translating languages [8,9].…”
mentioning
confidence: 99%
“…Today, education relies heavily on ICT, with new tools in the field of higher education [7][8][9]. For instance, distance learning is not a challenge anymore with off-campus students accessing learning resources using e-learning and m-learning tools [10][11][12][13][14]. In addition to this, AI is gaining interest as it can be used to execute tasks normally associated with human intelligence [15,16], such as social networking applications for learning, speech recognition, learning management systems (LMS), decision-making, cloud learning services, visual perception, mobile learning applications and translating languages [8,9].…”
mentioning
confidence: 99%
“…The education institutes in the South Pacific are integrating information literacy and digital literacy as part of their curriculum to improve the information literacy and digital literacy of their citizens. Furthermore, the higher education institutes are running their courses on distance and flexible learning as such the students require digital literacy skills to learn successfully via distance and flexible mode (Reddy et al , 2020a, Sharma et al , 2019a, b). Due to the COVID-19, pandemic education for all levels of education in the South Pacific has transited to online learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technology has become the backbone of communication, the work environment, and especially the health, government and education sectors in the country (Prasad et al , 2021; Reddy et al , 2019; Kumar and Mohite, 2017). The phenomena of the digital revolution are also impacting the behaviour of the individuals-the younger generation making digital technology part of their daily lives (Johnson et al , 2021; Prasad et al , 2021; Sharma et al , 2019b; Reddy et al , 2017; Sharma and Reddy, 2015). Due to the increasing dependence on digital devices and digital platforms, the education sector has evolved from traditional teaching and learning to a technology-driven education (Volpe, 2021; Alenzuela et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the developing countries the uptake of mobile learning has been shown to have improved the educational standards, made educational services available in remote areas and created cost efficient and flexible learning solutions (Bachmair & Pachler, 2015;Sharma et al, 2019;Reddy et al, 2020, Reddy et al, 2021b. A research conducted in Malaysia found that mobile phones are the most popular types of technology that are owned by students (Hussin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%